Pengaruh Menghafal Al Quran Terhadap Kecerdasan Spiritual Program Tahasus Madrasah Aliyah Tarbiyatut Tholabah Lamongan - Vika Madinatul Ilmi; Alya Khoironi Muhibbah; Dini Maulidha; Faziadatun Ni’mah; Feni Tamimul Ummah; Mayaly Maghfiroh; Shofwatul Fikriyyah; Eny Lathifah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study was to determine the quality of memorising the Qur'an and to determine whether or not there is an effect of memorising the Qur'an on Spiritual Intelligence. The research method is Quantitative with the type of case study by maximising Questionnaire Instruments, Interviews, Observation, and Documentation with a sample size of 42 Tahasus students at Mandrasah Aliyah Tarbiyatut Tholabah Lamongan. The results of this study indicate that there is a significant influence between memorising the Quran and Spiritual Intelligence. Spiritual Intelligence (Y) is influenced by the variable of memorising the Quran (X) by 62.60%, and the remaining 37.40% is influenced by other variables. Based on the magnitude of the effect of memorising the Quran on the Spiritual Intelligence variable, it proves that the factor of memorising the Quran is strong enough to predict Spiritual Intelligence.